2017
DOI: 10.1016/s2095-3119(16)61511-3
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of HPAI biosecurity measures: The Chinese broiler industry

Abstract: Highly pathogenic avian influenza (HPAI) contamination via wild birds and rodents poses a threat to food security and safety. As chicken meat comprises an increasing proportion of diet in China it is useful to determine whether broiler farmers are adopting wild bird and rodent controls to minimize the risk of HPAI impacts on food supply. Our study surveyed a cross sectional sample of 331 Chinese broiler farmers in six provinces. We find that only 47% of farmers (mainly farmers with large herds) adopted control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…From the above literature review and statistical analysis, we found that production patterns also affect farmers' adoption behavior. At the same time, dairy farmers with more adult cows would pay more attention to dairy production, and the possibility of adopting milk safety measures would be higher (Handschucha et al 2013;Huang et al 2017).…”
Section: Variables and Their Descriptive Statisticsmentioning
confidence: 99%
“…From the above literature review and statistical analysis, we found that production patterns also affect farmers' adoption behavior. At the same time, dairy farmers with more adult cows would pay more attention to dairy production, and the possibility of adopting milk safety measures would be higher (Handschucha et al 2013;Huang et al 2017).…”
Section: Variables and Their Descriptive Statisticsmentioning
confidence: 99%
“…It was similar to broiler breeders in China in which only 47% of them controlled the traffic by controlling wild birds and rodents from entering their farms. Birds and wild rodents could be intermediaries for the transmission of poultry, so they could be infected with viruses [7]. Breeders needed to avoid direct contact between poultry and livestock with disease sources.…”
Section: Traffic Controlmentioning
confidence: 99%
“…Only 47% of farmers-controlled traffic by controlling wild birds and rodents so they could not enter their farms. Birds and wild rodent animals can be an intermediary for the infection of chickens, so that livestock can be infected with the virus [8]. Farmers need to avoid direct contact between livestock, chickens with sources or carriers of disease.…”
Section: Good Traffic Controlmentioning
confidence: 99%